Correction: The synergic effect between Mo species and acid sites in Mo/HMCM-22 catalysts for methane aromatization. Issue 25 (20th June 2022) - Ma, Ding; Zhu, Qingjun; Wu, Zili; Zhou, Danhong; Shu, Yuying; Xin, Qin; Xu, Yide; Bao, Xinhe
Abstract : Correction for 'The synergic effect between Mo species and acid sites in Mo/HMCM-22 catalysts for methane aromatization' by Ding Ma et al., Phys. Chem. Chem. Phys., 2005, 7, 3102–3109, ; https://doi.org/10.1039/B502794B .